Automation of Constant Head Orifice Off-Take Structure - Ghazali, Hapida (2005)
The efficiency of irrigation for paddy cultivation depends very much on water supply and demand to be provided during the growing season. Due to complexity in operating water intake structure, the Constant Head Orifice (CHO) was developed to overcome the problems which required intensive labour. A CHO off-take structure is an important structure in the irrigation scheme to facilitate measurement and provide constant irrigation water supply.